Role of Biomaterials in Automation. Issue 1 (March 2021) - Fayomi, O. S. I.; Adedeji, A.A.; Agboola, O.; Ajala, M.O; Bolu, C.A; Banjo, S.O.; Udoye, N. E.
Abstract: Technology in its real sense is in an advanced state to an extent that automation is the present-day mode of operating machinery and equipment. This technique of operating or controlling a process using a highly automatic means via electronic devices thereby reducing the human interface to a minimum, if not rather than eliminating it completely. Transformation of the global workforce has already begun through automation with innovations of robotics, artificial intelligence remote connectivity, additive manufacturing and medical innovations employing the automated means of delivering or administering drugs and performing surgery on patients. In the present day, various forms of automation are increasingly taking over the place of human thereby, putting a threat to supplant it. The role of biomaterials in automation is the main objective in this discuss. The study revealed that metals play a major role in biomaterials due to its excellent thermal conductivity and mechanical properties.